2020
DOI: 10.1108/ijchm-03-2020-0219
|View full text |Cite
|
Sign up to set email alerts
|

Does climate for creativity mediate the impact of servant leadership on management innovation and innovative behavior in the hotel industry?

Abstract: Purpose Drawing from theory of organizational creativity, servant leadership (SEL), social exchange and social learning theories, this paper aims to propose a research model where climate for creativity mediates the influence of SEL on management innovation and innovative behavior. The model also investigates the linkage between innovative behavior and management innovation. Design/methodology/approach Data collected from Arab hotel employees in Palestine were used to gauge the aforesaid linkages through str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
99
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(143 citation statements)
references
References 80 publications
(110 reference statements)
7
99
0
5
Order By: Relevance
“…The goal of hotel industries is to offer high standard services, and the provision of these services is more likely to be achieved when employees are supported by morally strong leaders. Therefore, an ethical leader tries to establish an ethical climate that follows a normative acceptable code of conducts, motivating frontline employees to strive for service excellence and creativity [30].…”
Section: Ethical Leadership (El)mentioning
confidence: 99%
“…The goal of hotel industries is to offer high standard services, and the provision of these services is more likely to be achieved when employees are supported by morally strong leaders. Therefore, an ethical leader tries to establish an ethical climate that follows a normative acceptable code of conducts, motivating frontline employees to strive for service excellence and creativity [30].…”
Section: Ethical Leadership (El)mentioning
confidence: 99%
“…Thus, CSR promotes a work environment that has a significant impact on employees' innovative capability [32]. Moreover, different research studies have also established that the phenomenon of servant leadership promotes EIB [33][34][35]. However, it is not known from existing research studies how the concept of servant leadership and CSR-E can encourage the employees to display EIB.…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted by various researchers have investigated the effect of employees’ behaviors and found that servant leadership had a positive relationship with the motivational levels of employees, influenced their commitment levels and led them involve in extra role behaviors toward their organizations (Karatepe et al , 2020; Lapointe and Vandenberghe, 2018; Su et al , 2020). However, very few studies have examined the positive impact of servant leadership on employees’ IWB considering the mediating mechanisms (Karatepe et al , 2020; Zhu and Zhang, 2020). Servant leadership’s subsequent role is placing satisfaction of followers’ needs at the center of their efforts before even their own needs (Bouzari and Karatepe, 2017).…”
Section: Introductionmentioning
confidence: 99%